Patient-specific dynamic reference frame for navigation-assisted surgery in mandible: a novel noninvasive technical method - Wu, Jinyang; Jiang, Lai; Cheng, Yingqi; Zhang, Wenbin; Zhang, Jianfei; Gao, Xiaoyan; Xu, Xiaofeng; Zhang, Shilei (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectivesComputer-assisted navigation has been established as a valuable tool in oral and craniomaxillofacial surgery. However, the steep learning curve associated with mandibular navigation surgery has hindered its widespread adoption. This study introduces a non-invasive, convenient, and accurate navigation method for mandibular surgery and evaluates its clinical effectiveness.MethodsA modified patient-specific dynamic reference frame (PS-DRF) was designed and fabricated based on the patient’s lower jaw dental cast, integrating navigation technology with 3D printing. During surgery, the PS-DRF was securely affixed to the lower dentition, enabling automatic pair-point registration through fiducial localization via a navigation probe. The surgical procedure was conducted under real-time navigation guidance. ResultsPreoperative registration and intraoperative navigation were successfully achieved in this case. The navigation-guided mandibular surgery was completed without complications. Postoperative superimposition of the simulated virtual model and the actual surgical outcome demonstrated high accuracy, with a deviation of less than 2 mm. ConclusionThe PS-DRF system offers a convenient, effective, and adaptable approach by integrating navigation technology with 3D printing. This method has the potential to simplify navigation-assisted mandibular surgery and facilitate the broader clinical implementation of computer-assisted navigation in maxillofacial procedures.